Analisis dan Pemodelan Proses Bisnis Menggunakan Business Process Improvement (BPI) (Studi Kasus: Penginapan Griya Brawijaya) - Juara Hutagalung; Nanang Yudi Setiawan; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Lodging is a common thing that is needed by the community at this time, Griya Brawijaya is one of the Universitas Brawijaya business units which is also engaged in lodging services. In the current business process, there are some problems that affect consumer satisfaction and also Griya Brawijaya lodging company, such as the service process on orders that are still not optimal because the data collection system is not integrated so there is duplicated data, and also the checkout process rooms that are often late, then make consumers complain directly to the receptionist, this also happens because of a service mismatch with the SOP (Standard Operating Procedure). Therefore, in solving the problem requires analysis and evaluation, which is focused on business processes in order to improve and also maximize business processes at this time to make improvements to overcome any existing problems. So it takes business process modeling using BPMN (Business Process Modeling and Notation) then analyzes and evaluates the source of the problem using the RCA method (Root Cause Analysis) then makes improvements using the BPI (Business Process Improvement) method. Then simulations are carried out to find out the comparison between business processes that are running now (As-Is) with an improved business process (To-Be) so that any problems that exist at Griya Brawijaya lodging can be resolved.